Factors Determining the Relation between Firm Expenditure and Working Capital Management in Firms Listed in Tehran Stock Exchange - Dehcheraghi, Parvin Moradi; Kheirollahi, Farshid (International Journal of Economics and Financial Issues, 2017)
Currently firms’ liquidity status is in undesirable condition and due to inflation conditions governing the country, most of Iranian firms prefer to convert the cash fund into other assets and this cause that the firms fail meet debts deadlines and this damages the credit of organization. The experience has shown that one of major reasons which cause that most of firms sustain financial distress and finally, some of them end up with bankruptcy is lack of proper management of working capital. This paper aims to determine the relation between firm expenditure with working capital management in firms listed in Tehran Stock Exchange. Along this, firm expenditure include capital expenditure and operating expenditure as independent variables and Net Liquidity Balance (NLB) and Working Capital Requirement (WCR) are considered as criteria of working capital management and study dependent variables. In this paper, one also considers operating cash flow, sale growth, and long-term debt to equity ratio and stock market to book value ratio are considered as independent variables. Data used in this paper include a sample consisted of 128 firms listed in Tehran Stock Exchange over 2009-2013 period. Linear regression pattern in hybrid method is used for analyzing data and testing hypothesis. Results obtained from study hypothesis test based on regression analysis suggest that there is a reverse significant relation between firm expenditure including capital expenditure, operating expenditure with working capital management. Similarly, this conclusion is drawn that rate of firm growth and firm size play mediatory role in the relation between firm expenditure and net liquidity balance. Keywords: capital expenditure, Operating expenditure, working capital requirement, net liquidity balance, working capital management, JEL Classifications: G1, G2